Hemipteros asociados a orquideas silvestres - Diaz, A.=700 1 Abreu, N.; Martin, J.; Suarez, G.M.
(Es, En)
Ilus., 4 ref.
Keywords: ORCHIDACEAE; HEMIPTERA; INSECTA; HUESPEDES; CUBA; HEMIPTEROS ASOCIADOS; ORQUIDEAS SILVESTRES